A bibliometric study of Indian medicinal plant research: An analysis of quality research papers based on the web of science - Rahaman, Md Safiqur; Ansari, Khadeeja MN; Tewari, Lalit Tewari; Shah, Karnika (Qualitative and Quantitative Methods in Libraries; Vol 10 No 4 (2021): December issue 2021, 2022)
Many published resources on the topic can trace the research community's increasing interest in medicinal plant research. However, there is no systematic bibliometric review in the field of medicinal plants. This research's primary purpose was to analyze research output on the medicinal plant by the Indian researcher from 1977 to 2020 through a bibliometric perspective. To analyze and present the results based on bibliometrics indicators, namely yearly research trends, relevant journals, productive organization, prolific authors, authorship pattern, country collaboration level, and funding agencies. A total of 3911 quality research papers have been downloaded from the web of science. Data was analyzed with Microsoft excel, bibliometrics, and scientometric software, namely Bibexcel, VOSviewer, and Biblioshiny (RStudio). The study reveals that the year 2020 has the highest number of research papers (NP=376) in the medicinal plant, Journal of Ethnopharmacology (NP=125) found the leading contributed sources in the medicinal plant. Kumar A was the prolific author among Indian authors. Most of the researchers published their papers in the form of articles (89.70%), CSIR (NP=143) was the highest contributed organization in the field, and University Grants Commission India (NP=421) was the most influential funding agency on medicinal plant research in India. This bibliometrics analysis not providing the researchers' direction, but it extends helps to the policymaker and funding agencies.